Copper-mediated oxysulfonylation of alkenyl oximes with sodium sulfinates: a facile synthesis of isoxazolines featuring a sulfone substituent. Issue 12 (30th January 2017) - Wang, Li-Jing; Chen, Manman; Qi, Lin; Xu, Zhidong; Li, Wei
Abstract : A novel and efficient Cu(OAc)2 -mediated oxysulfonylation of alkenyl oximes with sodium sulfonates was developed. The reactions are easy to conduct, occur under mild conditions, and form a broad range of sulfone-substituted isoxazolines in good yields. Abstract : A novel and efficient Cu(OAc)2 -mediated oxysulfonylation of alkenyl oximes with sodium sulfonates was developed. The reactions are easy to conduct, occur under mild conditions, and form a broad range of sulfone-substituted isoxazolines in good yields.